Upaya Menghadapi Konflik dalam Manajemen Pendidikan di Madrasah - Setiawan, Farid; Kristiyanto, Risky; Setiawati, Ardhia; Ayuningtiyas, Indah; Abdullah, Muhammad Rizki (Lembaga Yasin AlSys, 2022)
The purpose of this study was to find out how to resolve conflicts in the administration of education in Madrasahs and the challenges faced in education management in Madrasas or schools. This is so that the author as a vocational teacher can find a solution to the conflict in education management in the madrasa that he must find when he becomes a teacher candidate. In this paper, the author uses a qualitative descriptive research method to obtain information. Because the information in this document describes efforts to manage conflict in the provision of education in madrasas or schools. Poor management will affect the development of schools, especially at this time the quality of education is still declining. The factors that influence the government are the obsolescence of science and technology due to globalization so that it gives birth to quality, directed, well-planned and well-organized schools. As is happening in Indonesia today, education is still developing unevenly, coupled with the impact of the 19th earthquake, making education management even more chaotic. Therefore, in the arrangement and management of teachers, teachers must carry out their responsibilities and obligations properly in school management in accordance with educational orientation.